The Development of an Integrated Thematic Learning Model Based on Islamic Values - Yogia Prihartini; Wahyudi Buska; Nurlaily Nurlaily (IJER (Indonesian Journal of Educational Research), 2023)
This research aims to develop an Integrated Thematic learning model based on Islamic values. This development research follows the steps of 4-D development, product testing of learning model development is carried out through validity, practicality and effectiveness. Because with an integrated thematic learning model based on Islamic values, students can learn various Islamic foundations as a basis that will be developed in learning materials according to the learning theme and linked to students' daily morals. The expected result of the research is the development of an integrated thematic learning model based on Islamic values that is valid, practical and effective. The results of the research on the development of thematic learning models based on Islamic values have proven that the thematic learning models based on Islamic values is a good learning model to be used in the implementation of learning at Mutiara Al Madani Islamic Elementary School Sungai Penuh Kerinci because there are nine values. Islamic education that was developed by the residents of Mutiara Al Madani Islamic Elementary School Sungai Penuh Kerinci namely religious, environmental care, social care, honesty, responsibility, curiosity, creative. Even though in integrated development based on other Islamic values such as love of peace, fond of reading, appreciating achievement, they focus on the nine programmed Islamic values and the development of Islamic values which is carried out continuously, integrated, consistent, implementable and enjoyable will have an impact on attitudes and moral behavior of students such as children accustomed to cleaning up leftovers without being ordered, respecting parents, speaking polite words, getting up at night to pray midnight, caring for friends and other positive characters. The development of thematic learning models based on Islamic values has implications for academic studies on classroom learning from various aspects such as: learning design in designing lesson plans, strategies, materials and evaluation, especially for the learning models used by educators in carrying out learning. This research has an impact on the development of theories regarding learning models for design, strategy, and evaluation of learning.